Sensory-based relational art therapy approach (S-BRATA) : supporting psycho-emotional needs in children with autism - Durrani, Huma (New York, NY : Routledge, 2021)
"This book bridges art therapy practice and research by presenting sensory-based relational art therapy approach (S-BRATA), a clinically tested framework for working with children with autism spectrum disorder (ASD) that explicitly addresses sensory dysfunction and its impact on impaired attachment. The author shows how art therapy can facilitate attachment while addressing sensory problems that might underlie impaired attachment shifting the focus from the behavioral to the emotional development of the child with autism. The book additionally challenges traditional aspects of art therapy practice, particularly the focus on the relational aspect of the intervention and not the art product. Not restrictive or prescriptive and with the potential to be adapted to other interventions, S-BRATA provides an explicit framework for doing art therapy with children on the spectrum that opens the scope of art therapy practice and encourages flexibility and adaptation. Clinicians, students, and parents alike will benefit from the text's clear outline for relational development with individuals on the spectrum and its emphasis on the importance of the psycho-emotional health of a child with ASD"--
OCLC-licensed vendor bibliographic record.
Keywords: Art therapy; Children with autism spectrum disorders; PSYCHOLOGY / Psychopathology / Autism; PSYCHOLOGY / Developmental / Child